Etude et analyse des précipitations annuelles et mensuelles dans la région de Tlemcen. - LATROCH, ABDELKADER (My University, 2021)
This work consists in carrying out the pluviometer study of the Tlemcen region in the period (2000-2020).To try to elucidate this problem, it is essential to analyze the term precipitation beforehand. We will try to answer some worrying and fundamental questions, among others: How is the rainfall in our region evaluated in space? Has there been a decrease in precipitation over the past decade? In this perspective, we help to study rainfall using statistical processing and analysis of drought indices. The analysis of the monthly averages has shown us that there is a shift in the months of the seasons; we can qualify its seasons as early because they no longer correspond to the reference established for a Mediterranean climate. The different seasons (winter, spring, autumn and summer) merge with each other. The calculations of the different indices have made it possible to say that we are facing an irregular climate with two dominant seasons. The rainfall variation interval is very wide. The extreme can be reached at any time of the year: when there is humidity or drought, both can reach a very high degree of severity.
Keywords: Climate; rainfall; drought; Tlemcen